Analisis Efisiensi dan Akurasi Penggunaan Aplikasi Gaji KPPN Terpusat dalam Penyaluran Gaji Induk yang Bersumber dari Anggaran Pendapatan dan Belanja Negara pada KPPN Bandung II - Juju Nuryanti; Fithri Dzikrayah (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The aim of this research is to analyze the accuracy and efficiency of the Centralized KPPN Salary Application in managing state finances, especially in terms of main salary distribution. This research uses a qualitative descriptive method with primary data sources in the form of interviews and secondary data in the form of documentation. The research results show that this application is able to increase efficiency through automation processes, reduce manual intervention, and speed up data reconciliation. Accuracy is also increased with an automatic validation system that ensures accuracy in calculating and recording salaries. Compared to manual mechanism, this application is able to reduce the potential for errors, speed up data processing, and optimize electronic document management.